HUBUNGAN PERAN KETUA TIM DENGAN KINERJA PERAWAT PELAKSANA DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI IRINA F RSUP PROF DR. R. D. KANDOU MANADO - Widodo, Widya N; Wungow, Herlina; Hamel, Rivelino S (JURNAL KEPERAWATAN, 2016)
Abstrack : Nurse’s performance is a nurse acts commited within an organization according to their respective responsibilities. The team leader as a professional nurse should be able to use a variety of leadership techniques such as planning, organizing, directing and monitoring. Team leader must be able to make decisions about the priorities of the planning and evaluation of nursing care. Nursing documentation is a record that contains all the information needed to determine the nursing diagnosis, nursing plan, implement and evaluate nursing actions, that arranged in the correct and accountable morally and legally. Aim of the Study: to identify the relationship between team leader’s role and nurse’s performance in documentation of nursing care. Methods: using observational analytic with cross sectional approach. The population are all nurses at inpatient department F in Prof. Dr. R. D. Kandou Manado Hospital and using total sampling technique that involved 30 nurses. The data collection tools that used in this study are questionnaire and observation sheets. Results: analysis was using Fisher’s Exact Test with a significance level of 95% (á=0.05) and shows that the p value is 0.003. Conclusion: there is a relationship between team leader’s role and nurse’s performance in documentation of nursing care at inpatient department F in Prof. Dr. R. D. Kandou Manado Hospital. Recommendations: for the managers of nursing in order to improve the resources of nursing through training and the seminar , also increased scrutiny so obtained documentation thoroughly. Keywords : Team Leader Role, Documentation, Nursing Care. Abstrak : Kinerja perawat merupakan tindakan yang dilakukan seorang perawat dalam suatu organisasi sesuai dengan tanggung jawabnya masing–masing. Ketua tim sebagai perawat profesional harus mampu menggunakan berbagai teknik kepemimpinan seperti perencanaan, pengorganisasian, pengarahan dan pengawasan, ketua tim harus dapat membuat keputusan tentang prioritas perencanaan dan evaluasi asuhan keperawatan. Dokumentasi keperawatan adalah suatu catatan yang memuat seluruh informasi yang dibutuhkan untuk menentukan diagnosis keperawatan, menyusun rencana keperawatan, melaksanakan dan mengevaluasi tindakan keperawatan yang disususn secara benar dan dapat dipertanggungjawabkan secara moral dan hukum. Tujuan Penelitian: untuk mengetahui hubungan peran ketua tim dengan kinerja perawat pelaksana dalam pendokumentasian asuhan keperawatan. Metode: observasional analitik dengan pendekatan cross sectional. Populasi adalah seluruh perawat di Irina F RSUP Prof. Dr. R. D. Kandou Manado. Teknik pengambilan sampel mengunakan total sampling dengan jumlah 30 sampel. Pengumpulan data menggunakan kuisioner dan lembar observasi. Hasil Penelitian: analisis menggunakan Fisher’s Exact Test dengan tingkat kemaknaan 95% (á=0.05) dan menunjukan nilai p=0.003. Simpulan: terdapat hubungan antara peran ketua tim dengan kinerja perawat pelaksana dalam pendokumentasian asuhan keperawatan, Saran: bagi manajer keperawatan agar dapat meningkakan sumber daya keperawatan melalui pelatihan dan seminar, juga meningkatkan pengawasan sehingga di peroleh pendokumentasian secara menyeluruh. Kata Kunci : Peran Ketua Tim, Pendokumentasian Asuhan Keperawatan